A aplicação do Trade Marketing em pequenas indústrias - Palmeira, Elaine Pinheiro (2014)
This dissertation has as its theme the Trade Marketing. The need for a realignment on distribution channel members relationship towards greater cooperation in achieving goals did the Trade Marketing arise. The implementation of its concepts to the company gives support and guidance to marketing and sales departments, providing better results for the organization and a solid and lasting relationship with the retailer, for that reason Trade Marketing was implemented in large multinationals. However, there is on the market the participation of small industries that, dispite of its strength and importance, must make great efforts to survive in a highly competitive market and to differentiate at the point of sale in order to win the consumer. In this context, the study investigated the implementation of Trade Marketing in small industry and its effects on the relationship with the retailer through SuaviPan case study, in which the analysis was done on the basis of the six variables of Trade Marketing Mix. It was noticed that even without owning a formalized or even know thoroughly the concept of Trade Marketing, the small industry applies its strategies on their way and within their possibilities, reinforcing the essence of Trade Marketing about operate to adjust the strategy, the structure and operation of the company to the distribution channels dynamics, which results in better service and more cost effective to its customers and, therefore, consumers